Les siphons en terre cuite du monde romain : l’exemple de l’aqueduc d’Almuñécar (Andalousie, Espagne) - Elena H. Sánchez López (Gallia)
The aqueduct that supplied the Roman city of Sexi Firmum Iulium (today Almuñécar, Spain) had a long siphon as the last section before arriving at the city centre. From the analysis of this structure, both through archaeological remains and medieval descriptions of the city, we can conclude that the siphon system had two remarkable technical peculiarities: it was a double siphon, where the two sections connected through a columnaria, an air elimination device located at the most problematic point in the layout of the water piping; and the pressure pipes were made of terracotta.The chosen material matched the recommendations made by Vitruvius, since he concluded that, by comparison with lead pipes, terracotta pipes were cheaper, faster to repair, and guaranteed higher quality water.Despite Vitruvius’ advice, terracotta pipes do not seem to have been the favourite choice of Roman engineers, who also used lead and stone pipes. Similarly, they were one of the options for carrying water around the rest of the system, including areas where water was not flowing under pressure. In attempting to determine whether the terracotta pipes used in the siphons were given any particular technical qualities to ensure pressure resistance, the paper compares pressure pipes with those used in open-surface systems, all from Roman aqueducts in Turkey. The analysis result shows that there is not a major difference in the dimensions of the pipes used with either function, which seems to indicate that the clay pipes used in the siphons were not made with any special characteristics.The text finally discusses the possible reasons behind the choice of terracotta over other materials in manufacturing siphon pipes.The analysis of Roman siphons, and more generally Roman aqueducts, produces different explanations. For example, in Patara (Turkey), a Vespasian restoration of the siphon after an earthquake involved the replacement of the terracotta pipes with stone ones. However, in the Magra Dag aqueduct in Pergamon (Turkey), while the open-surface channels were actually made using terracotta pipes, the siphon used lead, a situation very close to that identified at Oinoanda (Turkey), where the siphon used stone pipes. A similar combination of materials can also be found in other regions. It is the case of the Aqua Cornelia at Termini Imerese, where the Barratina siphon used lead pipes while the Tre Pietre siphon pipes were made of terracotta.It is difficult to determine the reasons for those choices, since most of the technical data of ancient siphons still elude us. However, the first explanation that comes to mind would relate to some kind of technical issue linked to pressure tolerance. But without knowing the exact route of the conduits along the siphon, it is not easy to determine the height of the hydrometric column and consequently the pressure borne by the pipes.Then there are also other possibilities. On the one hand, there is an economic explanation since, as Vitruvius advised, terracotta was the cheapest option. But on the other hand, the choice could also have been influenced by the chronology of the construction or repair of the siphon.